Paradigma Penelitian Dalam Jurnal Ilmiah Metodologi Penelitian Kuantitatif - Purba, Laila Khairunnisa; Fitriani, Diah; Andini, Widia (DIKLINKO JOURNALS PUBLISHER, 2022)
This journal reviews the research paradigm through the quantitative research paradigm. Paradigm is a perspective, a way of understanding, a way of interpreting, a framework of thinking, a basis of belief that gives direction to action. In solving problems, researchers are required to look from a perspective that is capable of being carried out by the researcher. Researchers collect data and analyze from the initial discovery of the problem and continue to the next stages, for example the problem formulation stage, theoretical analysis, data verification, and conclusions. The basis for positivistic thinking in an effort to find the truth is based on the size of the frequency of events or variations of objects. The research paradigm has several types, namely the positivist paradigm, interpretive paradigm, and critical paradigm. The quantitative research method is defined as a research method based on the positivism paradigm, which is basically used in researching certain populations and samples. The qualitative research paradigm adheres to a humanistic model because it makes humans as research subjects in the phenomena or events to be studied.